APPLICATION OF VISUALIZATION, AUDITORY, KINESTETHIC (VAK) LEARNING MODEL FOR INCREASING UNDERSTANDING ENERGY CONCEPT - Latifah Nur Khasanah; Hadi Mulyono; Retno Winarni (Universitas Sebelas Maret, 2018)
The purpose of this research is to improve the understanding of energy concept by applying Visualization, Auditory, Kinestethic (VAK) learning model in third grade students of SD Ta’mirul Islam Surakarta in academic year 2017/2018. The from of this research is Classroom Action Research (CAR) which the implementation is done with two cycles and each cycle there are two meetings. Eachcycle consists of four stages : planning, implementation, observation, and reflection. The subject of this research is the students of the third grade of SD Ta’mirul Islam Surakarta with the number of the students is 25 students. The techniques of collecting the data that used in this study are observation, interview, test, and documentation.The technique of validity test is the validity of content. The result of this research shows that there is an increase of value understanding the energy concept from pre-action value until the implementation of cycle II.